2022
DOI: 10.1186/s13048-022-01035-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitrified cryopreservation duration on IVF and neonatal outcomes

Abstract: Background In this study, we aimed to evaluate the impact of the duration of cryopreservation storage on embryo viability, implantation competence, pregnancy outcome and neonatal outcomes. Methods We retrospectively evaluated the outcomes of patients who underwent IVF with vitrified cryopreserved embryos between January 2004 and August 2019 by following the first frozen embryo transfer cycles within the study period. A total of 31,143 patients met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The authors concluded that, although this group had the shortest GA (38.1 ± 1.7 weeks), it had little impact on neonatal health and that the blastocysts could be preserved for a long time post-vitrification. In a recent study involving 31,143 patients, the cryopreservation period did not affect neonatal birth-weight, but low birth-weight was not likely to occur after cryopreservation > 1 year, and the male-to-female ratio in the > 2-year cryopreservation group was significantly lower than that in several groups with a cryopreservation time of < 2 years ( 34 ). They suggested that this difference may be because patients in the longest cryopreserved period group were the oldest, and most of the embryos transferred were of poor quality.…”
Section: Discussionmentioning
confidence: 98%
“…The authors concluded that, although this group had the shortest GA (38.1 ± 1.7 weeks), it had little impact on neonatal health and that the blastocysts could be preserved for a long time post-vitrification. In a recent study involving 31,143 patients, the cryopreservation period did not affect neonatal birth-weight, but low birth-weight was not likely to occur after cryopreservation > 1 year, and the male-to-female ratio in the > 2-year cryopreservation group was significantly lower than that in several groups with a cryopreservation time of < 2 years ( 34 ). They suggested that this difference may be because patients in the longest cryopreserved period group were the oldest, and most of the embryos transferred were of poor quality.…”
Section: Discussionmentioning
confidence: 98%
“…The embryo cryopreservation duration and its impact on pregnancy outcomes remain debated. Some studies [13,[29][30][31] suggest that the embryo cryopreservation duration does not significantly affect pregnancy outcomes, while others [32,33] indicate decreased survival and pregnancy rates with prolonged vitrification freezing. Our study shows that embryo cryopreservation duration for over 1 year specifically impairs pregnancy outcomes, consistent with the negative effects of extended freezing periods found in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal timing for embryo freezing and its impact on pregnancy outcomes remain debated. Some studies 29,30,31,32 suggest that the duration of frozen time does not signi cantly affect pregnancy outcomes, while others 33,34 indicate decreased survival and pregnancy rates with prolonged vitri cation freezing. Our study shows that freezing embryos for over one year speci cally impairs pregnancy outcomes, consistent with the negative effects of extended freezing periods found in other studies.…”
Section: Discussionmentioning
confidence: 99%